Increased levels of 5HT2A receptor mRNA expression in peripheral blood mononuclear cells of patients with major depression: correlations with severity and duration of illness. (19th May 2017) - Amidfar, Meysam; Kim, Yong-Ku; Colic, Lejla; Arbabi, Mohammad; Mobaraki, Gholamhossein; Hassanzadeh, Gholamreza; Walter, Martin
Abstract: Background: Neuroimaging, immunologic, and pharmacologic studies have emphasized the role of 5-HT2A and 5-HT3A serotonin receptors in the pathophysiology of major depression. Aim: The aim of this study was to measure the relative expression of 5-HT2A and 5-HT3A receptor mRNA in peripheral blood mononuclear cells (PBMCs) of patients with major depressive disorder (MDD). Method: 5-HT2A and 5-HT3A receptor mRNA expressions were examined in PBMCs of 25 medication-naïve-patients with MDD, 25 medication-free MDD patients, and 25 healthy controls. 5-HT2A and 5-HT3A receptor mRNA expressions were measured using real-time quantitative PCR. This study evaluated patients' clinical symptoms using the Hamilton Depression Rating Scale-17 items (HDRS) and the Beck Depression Inventory (BDI). Results: Relative 5-HTR2A mRNA expression was significantly higher in PBMCs of all MDD patients when compared with healthy controls ( Z = −3.875, p  < 0.05). However, there was no significant difference in the relative levels of 5-HTR3A mRNA expression in PBMCs of all MDD patients when compared with healthy controls ( Z = −1.328, p  > 0.05). MDD patients showed significant correlations between 5-HTR2A mRNA expression and HDRS scores ( r s = 0.902, p  < 0.001) and BDI scores ( r s = 0.878, p  < 0.001). Conclusion: This study showed that depressed patients, irrespective of treatment, have higher 5-HTR2A mRNA levels in PBMCs than healthy subjects. It also provided evidence that 5-HTR2A mRNA levels in PBMCs of MDD patients could be associated with the severity of depression and the duration of the illness.